Inequalities in health care and access to health services among adults with self-reported arterial hypertension: Brazilian National Health Survey - Deborah Carvalho Malta; Crizian Saar Gomes; Sheila Rizzato Stopa; Fabiana Martins Dias de Andrade; Elton Junio Sady Prates; Patrícia Pereira Vasconcelos de Oliveira; Sheila Aparecida Massardi Ferreira; Cimar Azeredo Pereira (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2022)
This study compared indicators of care and access to health services by adults who self-reported hypertension in 2013 and 2019, analyzing those indicators according to gender, age group, schooling level, and race/color. This is an analytic study with data from the Brazilian National Health Survey (PNS), conducted in 2013 and 2019 in Brazil. The indicators to care and access to health services by individuals with arterial hypertension in both surveys were compared. For 2019, those indicators were analyzed according to sociodemographic characteristics. This study estimated the proportions, prevalence ratio (PR), and their respective 95% confidence intervals (95%CI). In total, 60,202 individuals were evaluated in 2013 and 88,531 in 2019, of these 24.4% reported arterial hypertension in 2013 and 23.9% in 2019. Women received more medical care for hypertension within the last year (PR = 1.07; 95%CI: 1.04; 1.11), had the last physician appointment at an basic health unit (PR = 1.11; 95%CI: 1.05; 1.17) than men. About race/color, black people had more hospitalization for hypertension or some complication (PR = 1.2; 95%CI: 1.05; 1.38) and intense or very intense degree of limitation in performing daily activities (PR = 1.37; 95%CI: 1.06; 1.76). In 2019, inequalities were evidenced and worse indicators were observed for males, black, with low education and young age. Therefore, investments in the Brazilian Unified National Health System, as well as public policies and strategic actions are essential to reduce inequalities, promote health care.